A meta-analysis and systematic review of plant growth regulator use in blueberry production - Dick, Daniel; VanderWeide, Joshua (Frontiers in Plant Science, 2025)
Plant growth regulators (PGRs) include natural and synthetic plant phytohormones and other substances with the capacity to shape one or more aspects of plant growth and development at small concentrations. PGRs are commonly utilized in tree fruit and table grape production to reduce fruit set (thinning) and increase fruit size, coloration, and quality. However, use of PGRs in the production of berry crops, such as blueberry, is less common despite the abundance of production issues and the breadth of PGRs generally registered for fruit crops. This meta-analysis and systematic review discusses the past and current literature surrounding PGR use in blueberry production. First, we highlight the lack of PGRs registered and available to use in blueberry production relative to the increase in blueberry production value over the past decade. Next, we discuss the published literature on PGR use in blueberry species by production topic, including fruit set, berry mass and plant yield, ripening rate and harvest fruit quality, post-harvest fruit quality, and winter hardiness. Meta-analysis of qualifying PGR and production topic combinations revealed that gibberellic acid (GA3) and cytokinins (CKs) increase fruit set, CKs increase berry size, abscisic acid (ABA) and GA3 do not influence berry size, GA3 increases yield, and ABA does not enhance anthocyanin concentration. As global blueberry production continues to expand globally, PGR use will likely increase to address production issues and sustain production and fruit quality.